2006
DOI: 10.1111/j.1939-1676.2006.tb02900.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Platelet Function in Horses: Ultrastructure, Flow Cytometry, and Perfusion Techniques

Abstract: We studied equine platelet function and activation using ultrastructural examination, flow cytometry, and perfusion. The main aim of the study was to evaluate hemostatic mechanisms in horses using these techniques. Ultrastructural observations were done on resting and activated platelets. Flow cytometry was used to evaluate binding of antibodies to major platelet glycoproteins (GPIIb-IIIa, GPIV, and GPIb) and activation-dependent antigens (P-selectin and lysosomal integral membrane protein [LIMP]). Perfusion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 43 publications
3
29
0
7
Order By: Relevance
“…Finally, the platelet responses to thrombin (0.1 U/mL), as measured by aggregometry, were different. Consistent with previous studies [7, 2732], OCS − platelets showed markedly altered aggregation kinetics as compared to OCS + platelets.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Finally, the platelet responses to thrombin (0.1 U/mL), as measured by aggregometry, were different. Consistent with previous studies [7, 2732], OCS − platelets showed markedly altered aggregation kinetics as compared to OCS + platelets.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies of the structure of platelets from different species show that platelets from some species lack recognizable OCS structures and do not have the distinctive pattern of internal membrane staining when membrane-impermeant tannic acid is used as a stain [3–7, 22]. Based on previous reports and observations from our laboratory, we separated the platelets from six different species into OCS + (human, mouse and dog) and OCS − (horse, cow and camel) groups (Table III).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when compared to the gold standard and more specific indicator of platelet aggregation, turbidimetric aggregometry, platelet function was not inhibited during drug administration, suggesting that the collagen/epinephrine cartridge was not an accurate representation of platelet function in horse. In horses, epinephrine is not a consistent and potent platelet agonist; therefore, the collagen/epinephrine cartridge in the platelet function analyzer does not consistently stimulate platelet aggregation, limiting the clinical application of the collagen/epinephrine cartridge …”
Section: Discussionmentioning
confidence: 99%